Effect of Different Ratios of Glycerol and Erythritol on Properties of Corn Starch-Based Films - Wang, Bin; Xu, Xin; Fang, Youxin; Yan, Shouxin; Cui, Bo; Abd El-Aty, A. M. (Frontiers in Nutrition, 2022)
The demand for biodegradable products has increased; hence, a suitable method for producing green composites is essential. This study prepared corn starch-based films using the solution casting method, and the physicochemical properties of the prepared films were investigated using a mixture of glycerol (GLY) and erythritol (ERY) at different ratios (4:0, 3:1, 2:2, 1:3, and 0:4) as plasticizing agents. The crystallinity, hydrophilicity, mechanical properties, oxygen and water vapor, surface roughness, and thermal stability of corn starch-based films were analyzed using small-angle X-ray diffraction, water contact angle, automatic tensile testing machine, oxygen permeability tester and water vapor permeability analyzer, atomic force microscope, and thermogravimetric analyzer. With the increase in GLY ratio, the thickness, water-solubility, water content, water vapor permeability, elongation at break, oxygen permeability and V-shaped crystallization of the corn starch-based films increased. The tensile strength and the thermal stability decreased with increasing the GLY ratio. We developed a new plasticizer using glycerol and erythritol to improve the properties of starch films and provided the basis for the industrial production of corn starch-based films.